Reflections on the Fukushima Daiichi Nuclear Accident: Toward Social-Scientific Literacy and Engineering Resilience - Ahn, Joonhong; Carson, Cathryn; Jensen, Mikael; Juraku, Kohta; Nagasaki, Shinya; Tanaka, Satoru (Springer Nature, 2015)
Nuclear Engineering; Environmental Science and Engineering; Social Sciences, general